Lean Premixed Pre-Vaporized Combustion In A Swirl Stabilized Liquid Fuel Burner - Ahmad Nordin, Ahmad Faris (Universiti Sains Malaysia, 2022)
From transportation sector alone is known to be major contributors to pollutant emissions such as NOx, CO, UHC, CO2 and the main cause of environmental degradation. Lean Premixed Prevaporised combustion has been gaining attention amongst scientific communities due to its potential in reducing pollutant emissions. Similarly, fossil fuel reserves currently are depleting due to extensive exploitation for power generation, transportation, and automation purpose. Ethanol has attracted wide attention as a replacement fuel for conventional fuels because of its lucrative benefits. Despite that, no countermeasures or alternative solutions are provided for application in a developing country such as Malaysia. Commercially, such research and studies would be a big step for towards a cleaner and greener transportation in the near future. Hence, a study was conducted to investigate the LPP combustion chamber with a swirler running on gasoline-ethanol mixtures. Several compositions of gasoline-ethanol blends which are E10(gasoline 90%/ ethanol 10%), E20, and E30 were burned at an equivalence ratio of 0.9 and 0.5. Based on the experiment, the implementation of a swirler articulates intense mixing between air and fuel before combustion. This experiment was performed on a virtual platform using ANSYS Fluent as means to simulate the combustion phenomena with the desired operating parameters. Mass flow rate and equivalence ratio mainly influence the flame characteristic formation and pollutant emission. From the results, it suggests that at ULPP combustion mode further lowering of emissions of NOx, CO and CO2 is possible. In addition, findings showed that the effect of swirl facilitates the high-speed mixing of air and fuel composition which also results in near-complete combustion situations. However, as the weightage of the ethanol composition increases within the blended mixture and under lean conditions, thermal power output is decreasing. Surely these findings would help as an input in efforts of realizing this technology.